Analisis Manajemen Risiko TI Menggunakan Framework COBIT 5 Domain APO12 dan EDM03 - Al Fajri; Novriyanto; Nazruddin Safaat H; Muhammad Affandes (STMIK Budi Darma, 2023)
PT Perkebunan Nusantara V Pekanbaru is a state-owned enterprise or BUMN, operating in the field of oil palm and rubber plantations located in the city of Pekanbaru, Riau Province, PTPN V has utilized information technology in running the organization and business processes therein, there are risks- risks that will disrupt the application of information technology and even be detrimental to the company, such as the risk of technical specification errors, the risk of errors in self-estimated price calculations (HPS), the risk of errors in the Work Plan and Requirements (RKS) documents and the risk of server failure or network failure. Risk management is an effort for PTPN V as the basis for infrastructure in good risk management governance, the research was carried out with the aim of being able to carry out information technology risk management analysis and provide recommendations to harmonize risk management in information technology processes, using the COBIT 5 framework and appropriate domains, namely the APO12 and EDM03 domains, The data needed in this research is in the form of secondary data and primary data, in the EDM03 domain it is known that the capability value is 4.56, which means the company has reached capability level 5 (optimizing process), in the APO12 domain it is known that the capability value is 4.43, which means The company has achieved capability level 4 (predictable process). Recommendations are given for processes in the APO12 domain as the domain used for risk management, while for the EDM03 domain process as the domain for risk optimization in the procurement and IT sections of PTPN V Pekanbaru